Food processing and cardiometabolic risk factors: a systematic review - Francine Silva dos Santos; Mariane da Silva Dias; Gicele Costa Mintem; Isabel Oliveira de Oliveira; Denise Petrucci Gigante (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To systematically review the evidence for the association between food consumption according to processing and cardiometabolic factors in adults and/or the elderly. METHOD Two independent evaluators analyzed the electronic databases PubMed, Web of Science and Lilacs until December 2018. We used the following terms: (convenience foods OR food processing OR highly-processed OR industrialized foods OR minimally-processed OR prepared foods OR processed foods OR ultra-processed OR ultraprocessed OR ultra processed OR unprocessed) AND (metabolic syndrome OR hypertension OR blood pressure OR diabetes mellitus OR glucose OR glycaemia OR insulin OR cholesterol OR triglycerides OR blood lipids OR overweight OR obesity) AND (adult OR adults OR adulthood OR aged OR elderly OR old). We assessed methodological and evidence qualities, and also extracted information for the qualitative synthesis from the selected studies. RESULTS Of the 6,423 studies identified after removing duplicates, eleven met the eligibility criteria. The main food classification we used was Nova. The consumption of ultra-processed foods was positively associated with overweight and obesity, high blood pressure and metabolic syndrome. All articles included met more than 50% of the methodological quality criteria. The quality of evidence was considered moderate for the outcome overweight and obesity and weak for hypertension and metabolic syndrome. CONCLUSIONS The Nova food classification stands out in the area of nutritional epidemiology when assessing the effects of food processing on health outcomes. Although caution is required in the interpretation, the results indicated that the consumption of ultra-processed foods can have an unfavorable impact in the health of individuals.